Caracterização da arborização viária e sua influência no microclima urbano na escala do pedestre - Giacomeli, Daniele Cristina (Universidade Federal de São Carlos, 2011)
The absence of appropriate conditions for the movement of pedestrians on sidewalks is degrading our human relationships of urban life and therefore the quality of life. There are several factors that determined the current situation of urban public walk among them are the actions without appropriate guidelines for implementation of these, the presence of random equipment, the network of electricity supply, the underground networks and also the deployment of nonspecific and irregular vegetation along the sidewalk. In this context, degradation of public space and the search for the recovery of several research areas that have been developed. Among the topics covered are: inventory methodologies, projects to bring the public footpath to the population needs, planning of urban trees and their various relationships, among others. This study aimed to examine, at a fraction of urban public spaces of the relations of way (sidewalk), are determined by a length of permanence, through microclimatic, tree inventory of the area and questioning passers-by, in order to understand the influence of urban trees on the microclimate on the scale of the pedestrian.
Urban trees characterization and your influence on urban microclimate on the pedestrian scale
Keywords: Planejamento urbano; Arborização das cidades; Microclimas; Conforto térmico; Arborização urbana; Urban trees; Microclimate; Urban thermal comfort; ENGENHARIAS